Leucocyte‐ and platelet‐rich fibrin block for bone augmentation procedure: A proof‐of‐concept study. (10th April 2018) - Cortellini, Simone; Castro, Ana B.; Temmerman, Andy; Van Dessel, Jeroen; Pinto, Nelson; Jacobs, Reinhilde; Quirynen, Marc
Abstract: Aim: The objective of this proof‐of‐concept study was to investigate the effects of a new guided bone regeneration technique with a tissue engineering approach. Materials and Methods: This single cohort observational study evaluated the outcome of the leucocyte‐ and platelet‐rich fibrin (L‐PRF) Block for horizontal bone augmentation in the maxilla. The L‐PRF Block is prepared by mixing a particulated biomaterial with chopped L‐PRF membranes at a 50:50 ratio and adding liquid fibrinogen to glue all together. Horizontal augmentation was assessed linearly and volumetrically immediately after surgery and 5–8 months later by matching consecutive cone beam computed tomography (CBCTs). Results: Ten patients (mean age of 50.7 years [±17.2]) representing 15 sites with horizontal alveolar deficiencies were included. Superimposition of pre‐operative and posthealing CBCT scans showed an average linear horizontal bone gain of 4.6 mm (±2.3), 5.3 mm (±1.2) and 4.4 mm (±2.3), measured at 2, 6 and 10 mm from the alveolar crest, respectively. The volumetric gain was 1.05 cm 3 (±0.7) on average. The resorption rate after 5–8 months was 15.6% (±6.7) on average. Conclusions: L‐PRF Block may be a suitable technique to augment deficient alveolar ridges.